Analisis Uji Bending Pada Spesimen Serat Kulit Jagung Fiberglass Dengan Perpaduan Resin Lycal Menggunakan Variasi Metode Pembuatan Vacuum Bagging Dan Vacuum Infusion - Setiawan, Ferry; Amri, Chairul; Suroso, Indreswari; Anhar, Muh (Journal of Applied Mechanical Engineering and Renewable Energy, 2025)
This research aims to analyze the bending strength of composite materials based on corn fiber and fiberglass with Lycal resin, which are produced using two methods, namely vacuum bagging and vacuum infusion.Composite materials are increasingly being used in various industries because of their light and strong haracteristics. In this research, corn fiber was chosen as a natural reinforcement material because of its abundant availability and economic potential, while fiberglass was used as additional reinforcement to increase the strength of the material.The composite manufacturing process is carried out using two different methods, namely vacuum bagging and vacuum infusion, which are then tested using the ASTM-D 790 standard to determine the mechanical characteristics of the material, especially in terms of its ability to withstand bending loads. Apart from the bending test, material density calculations were also carried out to compare the weight and density of the two manufacturing methods.The test results show that the vacuum infusion method producescomposites with higher flexural strength than vacuum bagging. This is caused by a more even distribution of resin and minimal air trapped in the material structure during the vacuum infusion process. The composite produced from this method also has a lower density, making it lighter but still mechanically strong.It is hoped that this research can contribute to the development of natural fiber-based composite materials that are environmentally friendly and efficient, and have the potential to be applied to the aerospace industry, especially in the manufacture of UAV structures